Issues on the inclusion of Puntius denisonii (Day), a freshwater ornamental fish of global value, as Schedule-I species under the Wild Life (Protection) Amendment Act, 2021 of India - Jain, Atul Kumar; Mercy, T. V. A.; Jain, Abhinika (Frontiers in Marine Science, 2022)
The Puntius denisonii is popularly known as Miss Kerala in India or Denison barb or red-line torpedo barb in the global ornamental fish trade. The species is endemic to fast-flowing rivers and streams of the Western Ghats of India. The species was not very popular earlier in aquatic trade but has been in great demand in global aquarium trade. Once it was exhibited at AQARAMA 1997 at Singapore and ranked third under the new species category. The export of the species from India started in 1996-97 which increased progressively and constituting about 60-65% of a total of 1.44 million US$ worth of ornamental fish exported from India in 2007-08. Thereafter, it started declining and presently became negligible. It was attributed to depleting stocks of P. denisonii in rivers, and streams of Western Ghats. The species was recommended to be listed as endangered on IUCN red list in a CAMP workshop held at NBFGR, Lucknow, India in September 1997, owing to habitat degradation, and the declining number of mature individuals in wild. It was categorised as Vulnerable in 2009, Endangered in 2013, and Critically Endangered in 2015 under IUCN red list. The Department of Fisheries, Government of Kerala restricted the collection of smaller size fish from natural water bodies since 2008 to revive the wild stocks. The Government of India has now proposed to include P. denisonii along with other two freshwater fish species, Semiplotus semiplotus (Assamese kingfish), and Osteobrama belangeris (Manipur osteobrama) as Schedule-I species under Wildlife (Protection) Amendment Act, 2021 of India. The species listed under this Schedule are prohibited to be hunted throughout the county. The captive breeding technology of P.denisonii has already been developed in the country more than a decade back, and fish is being produced commercially at several farms presently including hatcheries of the Kerala government. The species is also being cultured and produced on a commercial scale by many ornamental fish farmers of Indonesia and supplied to the global ornamental fish trade at cheaper rates, and more colour strains.